STRATEGI SOLUTION FOCUSED BRIEF COUNSELING UNTUK MENINGKATKAN KEMATANGAN KARIER SISWA - Wiwin Winayawati, - (2022)
Adolescence is a tentative period of transition from children to adulthood, from the fantasy stage of childhood's career aspiration to the realistic decision-making stage in early adulthood. This implies that high school students who are in the 15-18 years age range still have difficulty in making career decisions. Career maturity in adolescence is needed because it will become the basic foundation of students' ability to analyze career opportunities. This study aims to test the effectiveness of the solution-focused brief counseling strategy to improve the students' career maturity. The study used a quantitative approach with a quasi-experimental method and a non-equivalent control-group research design. The sampling technique used was purposive sampling. The instrument used for data collection was the Career Maturity Inventory (CMI) Form C with a Likert scale model. The results of the study show that a solution-focused brief counseling strategy is effective for improving the students' career maturity. This study recommends that guidance and counseling teachers or counselors implement group counseling by using a solution-focused brief counseling strategy to improve students' career maturity through programs that are tailored to the needs and characteristics of students.